Instructions for a heatwave ebook A novel. - O'Farrell, Maggie (2013)
An unforgettable narrative—f rom the New York Times bestselling author of The Marriage Portrait and Hamnet— of a family falling apart and coming together with hard-won, life-changing truths about who they really are. “ Strange weather brings out strange behavior .” London, 1976. In the thick of a record-breaking heatwave, Gretta Riordan’s newly retired husband has cleaned out his bank account and vanished. Now, for the first time in years, Gretta calls her children home: Michael Francis, a history teacher whose marriage is failing; Monica, whose blighted past has driven a wedge between her and her younger sister; and Aoife, the youngest, whose new life in Manhattan is elaborately arranged to conceal a devastating secret. In a story that stretches from the Upper West Side to a village on the coast of Ireland, Maggie O’Farrell explores the mysteries that inhere within families, and reveals the fault lines over which we build our lives.